Synthesis and performance analysis of ammonium dinitramide - Rahman, Asad (2017)
Ammonium dinitramide as non-corrosive, high performance, and Eco-friendly propellant was first synthesized by Russians in early 1970s, and then independently in early 1990s by Stanford Research International. Since then, there has been increased interest in its synthesis and performance analysis. Therefore, this project was aimed to enhance the study of ADN and explore new areas of its application. This project has 3 objectives where syntheses, prilling, electrolysis of ADN were studied. In first objective, a new, modified ADN synthesis method was developed. This method was able to synthesize ADN at near-zero temperature by nitration of potassium sulfamate with mixture of nitric acid, sulfuric acid and trifluoroacetic acid. Once synthesized, parametric studies were performed to increase the reaction yield. It was developed by analyzing the existing ADN synthesis methods and their reaction mechanisms.